Third nerve palsy due to posterior communicating artery aneurysm: the importance of early surgery. Issue 8 (August 1987) - Feely, M; Kapoor, S
Abstract : The value of early, direct aneurysm clipping in restoring third-nerve function after palsy associated with a posterior communicating artery aneurysm is assessed.